2001
DOI: 10.1074/jbc.m102879200
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Forms of the Amyloid-β Precursor Protein Are Ligands for the Class A Scavenger Receptor

Abstract: Upon activation, platelets secrete a 120-kDa protein that competes for the binding and internalization of acetyl low density lipoproteins (AcLDL) by macrophages. From the amino-terminal amino acid sequence, amino acid composition, and immunoblot analysis, we identified the active factor in platelet secretion products as sAPP, an ␣-secretase cleavage product of the ␤-amyloid precursor protein (APP), that contains a Kunitz-type protease inhibitor (KPI) domain. We showed that both sAPP751 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…It is also possible that the immunostaining in gray matter could be the result of -sAPP uptake by glial cells, for instance during a scavenging process. sAPP has been shown to bind to the scavenger receptor and to be internalised in transfected CHO cells [27]. High expression levels of the scavenging receptor have been detected near amyloid plaques in AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the immunostaining in gray matter could be the result of -sAPP uptake by glial cells, for instance during a scavenging process. sAPP has been shown to bind to the scavenger receptor and to be internalised in transfected CHO cells [27]. High expression levels of the scavenging receptor have been detected near amyloid plaques in AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…The The low-affinity APP-induced TGF␤2-specific receptor is APP. To address whether the TGF␤2-specific receptor is APP itself or other unidentified proteins whose expression are induced by APP, we performed competition experiments by adding as a competitor larger amounts of soluble APP␣ of human APP695 (sAPP), corresponding to amino acids 1 to 612 of APP695 (the numbering follows that of Kang et al and Santiago-Garcia et al [17,41]), to binding assays (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The SR-A binds and internalizes microaggregates of the 42-amino acid form of A␤ in vitro (9). In addition, we recently reported that the SR-A binds secreted forms of APP (8). The A␤ peptide and secreted APP are major constituents of senile plaques and cerebrovascular deposits in patients with AD and Down's syndrome (31)(32)(33).…”
Section: Sr-a Mediates Macrophage Adhesion To the Extracellular Matrimentioning
confidence: 99%
“…In addition, the SR-A binds a limited number of native proteins. We recently showed that the ␣-secretase cleavage products of the three main isoforms of the amyloid precursor protein (APP695, APP751, and APP770) are ligands for the SR-A (8). The SR-A also binds the amyloid-␤ (A␤) peptide (9), another enzymatic cleavage product of APP and a major component of senile plaques in Alzheimer's disease (AD).…”
mentioning
confidence: 99%